2010
DOI: 10.1259/dmfr/97056817
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasonography with submentovertex films and computed tomography scan in the diagnosis of zygomatic arch fractures

Abstract: Objectives: The aim of this study was to compare ultrasonography with CT scan and submentovertex films in the visualization of zygomatic arch fractures. Methods: 17 patients, 10 men and 7 women, with suspected fracture of the zygomatic arch were studied. The data from CT and plain films were compared with the ultrasonographic findings (Aloka 3500 (Tokyo, Japan) ultrasound equipment with a 7.5 MHz transducer). The probe was situated over the fractured arch transversely to evaluate its whole length. All of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 11 publications
2
35
0
2
Order By: Relevance
“…6,8 It has been reported that high-frequency probes reveal subtleties of bone structure and high-resolution scanners reveal minor bone displacements up to 0.1 mm, although operator expertise should also be taken into account. 8 A 7.5 MHz linear probe was used in the present study and the results were consistent with the results of studies carried out by Mohammadi 17 and Thiede 2 in which a 10 MHz linear probe was used. Furthermore, our results are consistent with the results of Danter,18 in which a 20 MHz probe was used to evaluate nasal bone fractures.…”
Section: 314-16mentioning
confidence: 99%
See 2 more Smart Citations
“…6,8 It has been reported that high-frequency probes reveal subtleties of bone structure and high-resolution scanners reveal minor bone displacements up to 0.1 mm, although operator expertise should also be taken into account. 8 A 7.5 MHz linear probe was used in the present study and the results were consistent with the results of studies carried out by Mohammadi 17 and Thiede 2 in which a 10 MHz linear probe was used. Furthermore, our results are consistent with the results of Danter,18 in which a 20 MHz probe was used to evaluate nasal bone fractures.…”
Section: 314-16mentioning
confidence: 99%
“…4,5 CT has been considered as a gold standard and it is the procedure of choice for diagnosing complex facial fractures, especially mid-facial fractures. [6][7][8] However, CT techniques are expensive, are not readily available and provide a high patient exposure dose. Owing to the proximity of the eyes and the thyroid gland, there is an increased risk for cataract and thyroid carcinoma from X-ray exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is contraindicated in pregnant women and in patients with cervical spine injuries. It has traditionally been used in the diagnosis of orbital and ocular lesions, but its role in maxillofacial trauma was not well recognized till the 20th century [36][37][38][39]. McCann et al used ultrasound with 85 % accuracy in diagnosing fractures of the zygomatico-orbital complex (ZMC).…”
Section: Fracturesmentioning
confidence: 99%
“…Conventional radiography remains the standard imaging procedure, but water's view targeting the lateral nasal walls is prone to misinterpretation [5,6]. Computed tomography (CT) is considered a gold standard for diagnosing complex facial fractures, especially mid-facial fractures [7][8][9]. However, CT is expensive, not readily available, and exposes the patient to high doses of penetrating radiation [4].…”
Section: Introductionmentioning
confidence: 99%